Lice lipeurus caponis infestation in turkey and chicken in Ibadan, Nigeria (2005)
Louse infestation in chickens and turkeys in Ibadan is reported. The birds including guinea fowl were housed together fed on corn, guinea corn shaft and household left overs and left to roam together in an enclosed area in a semi intensive system type of management. Report was made on a sudden drop in egg production in the birds, which finally stopped in the chickens and turkeys. Clinical examination revealed massive lice infestation in the turkeys and chickens but the guinea fowls had no louse. Examination of blood samples from 47% of the birds revealed no haemoparasites and haomatological parameters were within normal range. The lice was identified to be Lipeurus caponis